Everyday resilience in district health systems: emerging insights from the front lines in Kenya and South Africa. Issue 2 (2nd June 2017) - Gilson, Lucy; Barasa, Edwine; Nxumalo, Nonhlanhla; Cleary, Susan; Goudge, Jane; Molyneux, Sassy; Tsofa, Benjamin; Lehmann, Uta
Abstract : Recent global crises have brought into sharp relief the absolute necessity of resilient health systems that can recognise and react to societal crises. While such crises focus the global mind, the real work lies, however, in being resilient in the face of routine, multiple challenges. But what are these challenges and what is the work of nurturing everyday resilience in health systems? This paper considers these questions, drawing on long-term, primarily qualitative research conducted in three different district health system settings in Kenya and South Africa, and adopting principles from case study research methodology and meta-synthesis in its analytic approach. The paper presents evidence of the instability and daily disruptions managed at the front lines of the district health system. These include patient complaints, unpredictable staff, compliance demands, organisational instability linked to decentralisation processes and frequently changing, and sometimes unclear, policy imperatives. The paper also identifies managerial responses to these challenges and assesses whether or not they indicate everyday resilience, using two conceptual lenses. From this analysis, we suggest that such resilience seems to arise from the leadership offered by multiple managers, through a combination of strategies that become embedded in relationships and managerial routines, drawing on wider organisational capacities and resources. While stable governance structures and adequate resources do influence everyday resilience, they are not enough to sustain it. Instead, it appears important to nurture the power of leaders across every system to reframe challenges, strengthen their routine practices in ways that encourage mindful staff engagement, and develop social networks within and outside organisations. Further research can build on these insights to deepen understanding.